Escape Room: An active methodology for postgraduate teaching - Tejero Claver, Blanca; Alarcon Martínez, Virginia; Garrido Sáez, Neus (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Given the lack or decrease in the motivation of university students, teaching and with it the University finds itself in the position of putting into practice new, more active and motivating methodologies that allow students to have a more protagonist role in the teaching process and learning than they have had so far. This article presents an experience that consists of the design of an online Escape room framed in the Master in Special Education. The objective is to motivate students and facilitate learning of the subject.